The AK Party’s Islamic Realist Political Vision: Theory and Practice - Mufti, Malik (2014)
The currently governing Turkish AK Party’s reformist agenda at home and its increasingly assertive policies abroad, like the “soft” and “hard” power elements of its foreign policy, reflect a remarkable coherence and continuity in the political vision of the party leadership. That vision—a contemporary manifestation (sometimes described as “neo-Ottomanism”) of an older tradition of Islamic realism—is explicated through a detailed analysis of the speeches and writings of the main AK Party leaders, as well as of their opponents within the Islamist movement, and correlated with actual policy practice. It is further suggested that the AK Party’s preoccupation with its traditional secular-nationalist (Kemalist) adversaries has left it unprepared to confront an even more formidable looming challenge: liberalism.